An Americanization of musics in the early history of Philippine recordings 1900s to 1930s. - Decenteceo, Lisa Veronica D.L
This paper is a preliminary research into the subject of the Philippine recording industry. This research is the availability of the musical examples and the sources for catalogues and listings and recordings. This provides reference for the timeline from 1910s to 1930s